PERKEMBANGAN MOTIF BATIK WALANG JATI KENCONO DI GUNUNGKIDUL YOGYAKARTA - I Made Sukanadi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
Walang Jati Kencono batik motif has been certified industrial design rights obtained by gunungkidul district government used as uniform fabric of school students from paud, elementary, junior high, and high school/ vocational school level that must be produced by the batik craftsman community in Gunungkidul. Walang Jati Kencono batik motif is also the uniform of officials in Gunungkidul Regency. Since the enactation of this motif into gunungkidul batik character continues to undergo changes and developments, both in shape, technique, and coloring results. The purpose of this research is to know the source of the idea of the form, and the development of batik walang in Gunungkidul seen from the beginning was created until now used by gunungkidul people even outside people who are interested in the motif of batik walang. Research uses qualitative descriptive methods, with data collection using observation, interview, and documentation techniques, then the research instruments are the researchers themselves assisted by observation guidelines, interviews, and documentation. Validity of data with triangulation and persistence of observation, while data analysis techniques use the stages of data reduction, data presentation, and conclusion withdrawal. The results found from this study are: (1) Knowing the idea of the shape and development of Walang Jati Kencono batik motifs that are programmed as a characteristic uniform for students in Gunungkidul and strengthening local batik in order to drive the growth and empowerment of batik industry in Gunungkidul. Keywords: Batik, Motif Walang Jati Kencono, Gunungkidul, Craftsman